2006
DOI: 10.1038/emm.2006.27
|View full text |Cite
|
Sign up to set email alerts
|

An antioxidant modulates expression of receptor activator of NF-κB in asthma

Abstract: Oxidative stress plays critical roles in airway inflammation that is usually accompanied by increased vascular permeability and plasma exudation. VEGF increases vascular permeability and leads to airway inflammation. In addition, VEGF has been shown to enhance receptor activator of NF-κB (RANK) expression in endothelial cells. An aim of the study was to determine the potential role of antioxidant in the regulation of RANK expression in murine model of asthma. We have used a C57BL/6 mouse model of allergic asth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 43 publications
0
18
0
2
Order By: Relevance
“…We demonstrated ROS generation in human PBB that had released significantly more mediators when challenged with diesel exhaust particles compared with nonchallenged cells (35). Some evidence indicates that allergic and inflammatory skin diseases like atopic dermatitis, urticaria and psoriasis are mediated by MC-initiated oxidative stress (36) while recent studies suggest antioxidants can reduce asthma symptoms in mice (37,38). Previous studies have demonstrated that ROS, possibly from MC, play a significant role in the pathogenesis of a number of disorders such as inflammation, rheumatoid arthritis, asthma, psoriasis, urticaria, and contact dermatitis (39).…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated ROS generation in human PBB that had released significantly more mediators when challenged with diesel exhaust particles compared with nonchallenged cells (35). Some evidence indicates that allergic and inflammatory skin diseases like atopic dermatitis, urticaria and psoriasis are mediated by MC-initiated oxidative stress (36) while recent studies suggest antioxidants can reduce asthma symptoms in mice (37,38). Previous studies have demonstrated that ROS, possibly from MC, play a significant role in the pathogenesis of a number of disorders such as inflammation, rheumatoid arthritis, asthma, psoriasis, urticaria, and contact dermatitis (39).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups found decreased mitochondrial dysfunction and oxidative stress in asthmatic mice treated with antioxidants [95-105]. For example, using a C57BL/6 mouse model of allergic asthma, Lee et al .…”
Section: Therapeutic Approaches To Asthmamentioning
confidence: 99%
“…For example, using a C57BL/6 mouse model of allergic asthma, Lee et al . [95] studied the role of antioxidants in regulating the receptor activator of NF-kappaB expression. They evaluated the effects of the vascular growth factor receptor inhibitor and L-2-oxothiazolidine-4-carboxylic acid (a prodrug of cysteine), on the receptor activator of NF-kappaB mRNA expression.…”
Section: Therapeutic Approaches To Asthmamentioning
confidence: 99%
“…Increased ROS generation, which results in an imbalance between oxidative forces and the antioxidant defense systems, has been implicated in the pathogenesis of asthma (Rahman et al, 1999;Dworski et al, 2000;Rahman et al, 2000;Lee et al, 2006Lee et al, , 2007Kirkham et al, 2006). ROS are capable of eliciting a variety of pathological changes, including the peroxidation of lipids, proteins, and DNA and the generation of chemoattractants, as well as enhancements of AHR, airway secretion, and vascular permeability in asthmatic airways (Barnes et al, 1990;Henricks et al, 2001;Andreadis et al, 2003).…”
Section: Introductionmentioning
confidence: 99%